Suicide risk in chronic heart failure patients and its association with depression, hopelessness and self esteem - Korkmaz, Hasan; Korkmaz, Sevda; Cakar, Mustafa (Elsevier Sci Ltd, 2019)
Heart failure is a chronic disease that impairs the quality of life and leads to several psychiatric disorders, especially depression and anxiety. The present study intended to investigate suicide risk and its association with depression, hopelessness and self-esteem in patients with chronic heart failure. 32 patients with chronic heart failure and 32 healthy control subjects with similar sociodemographic attributes were included in the present case control study. Sociodemographic data form, Beck Hopelessness Scale (BHS), Beck Depression Inventory (BDI), Rosenberg Self-Esteem Scale (RSE) and Suicide Probability Scale (SPS) were applied to all subjects. It was determined that the BHS (11.4 +/- 3.74 vs. 4.8 +/- 4.02, p < 0.001), BDI (22.2 +/- 11.9 vs 9.2 +/- 7.6, p < 0.001) and SPS (67.6 +/- 15.9 vs 59.2 +/- 10.9, p = 0.018) scores were statistically higher in the patient group when compared to the control group. It was also established that the selfesteem of subjects in the patient group was lower when compared to the control (p < 0.001). A positive correlation was determined between the SPS and BHS, and BDI and RSE scores (p < 0.001). Suicide risk was higher among the patients with heart failure when compared to the control group. This increase in suicide risk significantly correlated with high levels of hopelessness, depression, and low self-esteem in the patient group. Heart failure is one of the chronic diseases that increases suicidal ideation. The identification of suicidal ideation in the present patient group facilitated both the prevention of suicidal behavior and positive contribution to treatment. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Heart failure; Suicide risk; Self-esteem; Hopelessness